Temporal Distribution And Composition Of Phytoplankton In The Southern Part Of Caspian Sea In Iranian Waters From 1994 To 2007 - Khenari, Ali Ganjian (2011)
Caspian Sea is the largest inner water body on the earth underwent sharp changes in its ecosystem during the recent decades of the twenty century. They were caused by natural eg. transgression of the sea level, climate change, increase of fresh water inflow and anthropogenic factors eg. pollution, invasion of ctenophore Mnemiopsis leidyi and illegal fishing for sturgeons at sea. All that led to significant change in hydrological regime; modify the food base, abundance and biomass of biological resources and bio-productivity of the sea. Long-term qualitative and quantitative characteristics of phytoplankton community structure and biomass were investigated in from 1994 to2007.